A Network Analysis of Post-traumatic Stress Disorder Symptoms and Correlates During the COVID-19 Pandemic - Jiang, Wanyue; Ren, Zhihong; Yu, Lixia; Tan, Yafei; Shi, Congrong (Frontiers in Psychiatry, 2020)
Abstract Background and Objective: The Coronavirus disease 2019 (COVID-19) outbreak has been suggested as a collective trauma, which presents a continuing crisis. However, the specific posttraumatic implication of this crisis has not been adequately studied yet. The current study was aimed to ascertain the most central symptom and the strong connections between symptoms of posttraumatic stress disorder (PTSD). At the same time, exploring the relationship between covariates and the network of PTSD symptoms by taking sex, anxiety, depression, suicidal ideation, quality of life, and social support as covariates, which may help us to know the arise and maintenance of PTSD symptoms and give specified suggestions to people under the shadow of COVID-19. Method: The Posttraumatic Stress Disorder Checklist for DSM-5 was used to assess the PTSD symptoms extent of 338 healthy participants over the past month. Networks were analyzed using state-of-the-art regularized partial correlation models. In addition, the centrality of the symptoms and the robustness of the results were analyzed. Results: The network analysis revealed that the especially strong connections emerged between avoidance of thoughts and avoidance of reminders; hypervigilance and exaggerated startle response; intrusive thoughts and nightmares, flashbacks and emotional cue reactivity, and detachment and restricted affect. The most central symptoms were self-destructive/reckless behavior. Incorporation of covariates into the network revealed the strong connections path between self-destructive /reckless behavior, and loss of interest and depression. Conclusion: Self-destructive/reckless behavior was the most central symptom in the network of PTSD symptoms related to the COVID-19 pandemic, which as an important target of interfere may have great benefits.